2000
DOI: 10.1007/s004670050798
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-sensitive nephrotic syndrome associated with Kimura disease

Abstract: We report an 11-year-old Japanese boy with Kimura disease and associated nephrotic syndrome. Before the diagnosis of Kimura disease was established, the patient had three episodes of swelling on the left cheek with subsequent nephrotic syndrome. Steroids were effective for both conditions. However, both conditions recurred within months of discontinuation of steroids. For the fourth episode of swelling on the left cheek, cyclosporine (CsA) was used. The subcutaneous tumor responded to CsA and disappeared withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…The Th2 cell, which is the main factor in the late-phase response in the allergic process, plays the major role in the production of cytokines, including IL-4 and IL-13, both of which regulate IgE and IL-5 [14]. Nakahara et al [15] reported elevated IL-5 levels in a patient having steroid-sensitive nephrotic syndrome. These authors concluded that the Th2 cell should be the major factor for the development of Kimura's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Th2 cell, which is the main factor in the late-phase response in the allergic process, plays the major role in the production of cytokines, including IL-4 and IL-13, both of which regulate IgE and IL-5 [14]. Nakahara et al [15] reported elevated IL-5 levels in a patient having steroid-sensitive nephrotic syndrome. These authors concluded that the Th2 cell should be the major factor for the development of Kimura's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the steroid response, especially in pediatric patients, Nakahara et al [15] reported recently that a steroid-sensitive nephrotic syndrome is associated with Kimura's disease, and Rajpoot et al [3], also recently, reported steroid-resistant nephrotic syndromes in children who developeded end-stage renal failure later and in whom kidney histopathology revealed mild to moderate mesangial hypercellularity with an increase in mesangial matrix. Reports of adult patients also revealed various histopathologies of the kidney in those who had nephrotic syndrome associated with Kimura's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose cyclosporine combined with low-dose prednisolone is a recent trend in the treatment of nephrotic syndrome. 17,20 Renal biopsy demonstrated minimal glomerular change on light microscopy and no glomerular deposition by fluorescent immunohistochemistry in the present patient. Glomerular IgE deposition in this patient remains unknown because routine fluorescent immunohistochemical staining did not include IgE.…”
Section: Discussionmentioning
confidence: 86%
“…Local irradiation has been successful in controlling local disease, with few recurrences [19], but has been used mainly when other methods have failed to give control, and is not recommended in young patients [20]. Cyclosporin A has also been used successfully [21]. Treatment needs to be undertaken with the knowledge that the clinical course is benign, and no malignant transformation of Kimura disease has been described.…”
Section: Discussionmentioning
confidence: 98%